2002
DOI: 10.1007/s00429-002-0250-0
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin-containing neurons mediate the feedforward inhibition of rat rubrospinal neurons

Abstract: The calcium-binding protein, parvalbumin and glutamic acid decarboxylase immunohistochemistry were used to locate candidate neurons mediating the inhibition of rat rubral neurons. A group of cells with small to medium-sized cell bodies that reacted positively to both were found in the red nucleus and its immediate vicinity. At the caudal nuclear level, these neurons gathered in the reticular formation, the pararubral area dorsolateral to the nucleus. As the nucleus expanded in size rostrally these neurons star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The properties of PV-containing interneurons are particularly well suited to imposing temporal precision (Freund, 2003) and PV-containing or fast-spiking interneurons are the main mediators of feedforward inhibition in many brain areas (Liu et al, 2002; Mallet et al, 2005; Daw et al, 2007). Maintaining synchrony of release throughout trains of presynaptic activity is clearly vital for carrying out this function.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of PV-containing interneurons are particularly well suited to imposing temporal precision (Freund, 2003) and PV-containing or fast-spiking interneurons are the main mediators of feedforward inhibition in many brain areas (Liu et al, 2002; Mallet et al, 2005; Daw et al, 2007). Maintaining synchrony of release throughout trains of presynaptic activity is clearly vital for carrying out this function.…”
Section: Discussionmentioning
confidence: 99%
“…It condensed into a gluey ball at the end of the micropipette immediately (Tseng et al. 1996; Liu et al. 2002) and applied into the C7–T1 DRGs of animals (Table 1) 7 days before they were sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…For application, the tracer, which was flaky when dry, was applied by touching it to the tip of micropipette moisturized with water vapor, for instance, over hot water, as it was highly hygroscopic. It condensed into a gluey ball at the end of the micropipette immediately (Tseng et al 1996;Liu et al 2002) and applied into the C7-T1 DRGs of animals (Table 1) 7 days before they were sacrificed.…”
Section: Anterograde Labeling Of Sensory Fibersmentioning
confidence: 99%
“…In an additional analysis aimed at demonstrating the variability of the nNOS expressed in the axotomized neurons over time, the ratio of the OD of each neuron to the mean of the contralateral control neurons of the same section was sorted into several categories from low to high and compared. To evaluate the effect of l-NAME treatment on brainstem-axotomized RS neurons, neurons with identifiable nuclei in the injured and the contralateral control RN in Cresyl violet-stained sections of the caudal RN were counted since this area contained exclusively RS neurons (Tseng et al 1995(Tseng et al , 1996aLiu et al 2002). In our hands, the identification of shrunk-axotomized RS neurons was straightforward because they were retrogradely labeled in all C2-and T10-axotomized animals studied while in brainstem-axotomized animals, glial markers were used to distinguish between neurons and glial cells (Liu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Data are means€SE. Note that the percentages of RS neurons surviving the axotomy are from a preceding study (Liu et al 2003); the data for survival ratio in the 4 days and 8 weeks columns are from animals 2 days and 10 weeks following lesion In this study we found that almost all RS neurons, 95% and 97% of those in the caudal RN (Liu et al 2002) respectively, increased their nNOS expression following C2 and brainstem axonal injury. The intensity of nNOS expression appeared to be axotomy distance-dependent, for in general L-RS neurons expressed higher levels of nNOS than C-RS neurons following C2 tractotomy, which might also reflect the fact that the C2 lesion removed longer segments of the axons of L-RS neurons than C-RS neurons (Tseng et al 1996a).…”
Section: Mn and Cu/zn-sod Expressions In Rs Neurons Following Axotomymentioning
confidence: 93%